2007
DOI: 10.1093/jac/dkl553
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile colitis that fails conventional metronidazole therapy: response to nitazoxanide

Abstract: Nitazoxanide appears to provide effective therapy for patients with C. difficile colitis who fail treatment with metronidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(61 citation statements)
references
References 34 publications
(37 reference statements)
0
58
0
3
Order By: Relevance
“…NTZ is not cross resistant with metronidazole, although their spectra against parasites and anaerobic bacteria are similar, and resistance to NTZ was not selected in H. pylori in vitro or in a clinical trial (251). Due to its anti-C. difficile activity and good safety and tolerability profile in humans, NTZ has been studied for the treatment of CDAD (266,267).…”
Section: Targeting Substrates and Cofactorsmentioning
confidence: 99%
“…NTZ is not cross resistant with metronidazole, although their spectra against parasites and anaerobic bacteria are similar, and resistance to NTZ was not selected in H. pylori in vitro or in a clinical trial (251). Due to its anti-C. difficile activity and good safety and tolerability profile in humans, NTZ has been studied for the treatment of CDAD (266,267).…”
Section: Targeting Substrates and Cofactorsmentioning
confidence: 99%
“…4,[35][36][37][38][39][40] Each of these drugs is approved in the United States for other types of gastrointestinal infections, and some clinicians have used either alone or in combination with metronidazole or vancomycin in patients with severe or recalcitrant CDAD. There are several small case reports addressing the potential efficacy of using adjuvant agents such as i.v.…”
Section: Management Of Cdadmentioning
confidence: 99%
“…Newer approaches include long, tapered or pulsed courses of vancomycin, as well as combination or sequential dosing with either rifaximin or nitazoxanide. [1][2][3][4][5]30,[35][36][37][38][39][40][41][42][43] An algorithm outlining our own approach is shown in Figure 2.…”
Section: Management Of Cdadmentioning
confidence: 99%
“…At 31 d after starting treatment, a sustained response was noted for 58% of patients treated with metronidazole vs 66% for the 7-d course of nitazoxanide and 74% for the 10-d course (P = 0.34). Musher et al [114] also reported the use of nitazoxanide in 35 patients that failed to respond to metronidazole after 14 d of therapy or who had prompt recurrence on at least two occasions after an initial response. They noted that 74% of patients responded, however, 7 of the 26 recurred, leaving an overall cure rate of 54%.…”
Section: Nitazoxanidementioning
confidence: 99%